2020
DOI: 10.1155/2020/5328031
|View full text |Cite
|
Sign up to set email alerts
|

NLRC3 Delays the Progression of AD in APP/PS1 Mice via Inhibiting PI3K Activation

Abstract: NLRC3 inhibits inflammatory responses. Neuroinflammation induces and accelerates the onset of Alzheimer’s disease (AD). This study is aimed at investigating whether NLRC3 plays a role in neuroinflammation, Aβ accumulation, and neuroprotection in AD mice. 12-month-old APP/PS1 transgenic and C57 mice were used for studies in vivo. In vitro, organotypic hippocampal slices were cultured. We found that the expression of NLRC3 was downregulated in the brain tissues of APP/PS1 mice. Mice in the APP/PS1 group had a si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Dietary supplemented baicalin zinc reduced DON-induced expression of p-Nrf2 and HO-1 in the piglets intestine (Zha et al 2020a ). Similar effect was observed for the complex of baicalin copper in another study (Zha et al 2020b ). Grape seed proanthocyanidin extract increased the expression of Nrf2 and its downstream genes decreased in the response to oxidative stress triggered by ZEA in murine liver and Sertoli cells (Long et al 2016 , 2017 ) as well as AFB1 induced oxidative stress and inflammation in broilers (Rajput et al 2019 ).…”
Section: Natural Antioxidantssupporting
confidence: 88%
“…Dietary supplemented baicalin zinc reduced DON-induced expression of p-Nrf2 and HO-1 in the piglets intestine (Zha et al 2020a ). Similar effect was observed for the complex of baicalin copper in another study (Zha et al 2020b ). Grape seed proanthocyanidin extract increased the expression of Nrf2 and its downstream genes decreased in the response to oxidative stress triggered by ZEA in murine liver and Sertoli cells (Long et al 2016 , 2017 ) as well as AFB1 induced oxidative stress and inflammation in broilers (Rajput et al 2019 ).…”
Section: Natural Antioxidantssupporting
confidence: 88%
“…Mounting evidence indicated that in ammation may affect mitochondrial function, membrane polarity and oxidative phosphorylation, which may further lead to oxidative stress and apoptosis [11,[52][53][54]. Microglia and astrocytes are main mediators of in ammation in the brain [55]. In our study reported here, the EDA administration signi cantly decreased microglial activation and attenuated astrocyte dysfunction.…”
Section: Discussionsupporting
confidence: 58%
“…Mounting evidence indicated that inflammation may affect mitochondrial function, membrane polarity and oxidative phosphorylation, which may further lead to OS and apoptosis [ 11 , 65 67 ]. Microglia and astrocytes are main mediators of inflammation in the brain [ 68 ]. In our study reported here, the EDA administration significantly decreased microglial activation and attenuated astrocyte dysfunction.…”
Section: Discussionmentioning
confidence: 99%